Relationship of Procrastination with Self-Efficacy and Job Performance among University Educators - Muhammad Ayub; Zahidullah; Kainat Zia; Zeeshan Ahmad; Mazhar Hussain (Indus Journal of Social Sciences, 2025)
This study investigates the relationship between procrastination, self-efficacy, and job performance among university educators. A total of 110 participants (73 males and 37 females) were recruited using a purposive sampling technique. Data was collected using three standardized instruments: the General Procrastination Scale, the New General Self-Efficacy Scale, and the short version of the Self-Assessment Job Performance Scale. The findings revealed a significant negative correlation between procrastination and job performance, indicating that higher levels of procrastination were associated with decreased job performance among university educators. Moreover, self-efficacy demonstrated a positive association with job performance, suggesting that individuals with greater confidence in their capabilities performed better professionally. Notably, unmarried educators exhibited superior job performance and self-efficacy compared to their married colleagues. Furthermore, age-related differences were observed, with educators aged 47 to 57 demonstrating significantly higher self-efficacy and job performance than those in the 25 to 35 and 36 to 46 age groups. These results underscore the detrimental impact of procrastination on academic job performance and highlight the critical role of self-efficacy in enhancing professional outcomes. The findings also suggest that demographic factors, such as marital status and age, influence job performance and self-efficacy levels among university educators. Addressing procrastination through targeted interventions may contribute to improved job efficiency and overall institutional productivity.